A toxicomania e o circuito-curto da pulsão : uma outra vicissitude - Rodrigo Pardini Guedes (2022)
The tesis proposes another vicissitude for the instinct in the face of the discontrol produced by toxicomania. The four destinies proposed by Freud in 1915 are not enough when the psychic and the somatic are affected by the excess of the drugs. Therefore, the subject-matter proposed is: when the addict breaks up with the phallus, adheres the consistent object-drug and keeps the absolut Other, it produces a small-circuit for the instinct.